Mechanical properties and failure analysis of laminated magnesium-intermetallic composites - Marek Konieczny (AIMS Materials Science, 2022)
Laminated Mg-intermetallic composites were successfully fabricated by reaction synthesis in vacuum using 1 mm thick magnesium sheets and 0.25 mm thick copper foils. The final microstructure consisted of alternating layers of a hypoeutectic alloy containing crystals of CuMg2 and eutectic mixture of CuMg2 and solid solution of copper in magnesium and unreacted magnesium. The mechanical properties and fracture behavior of the fabricated composites were examined under different loading directions through compression, three-point bending and impact tests. The results indicated that the composites exhibited anisotropic features. The specimens compressed in the parallel direction failed by cracking along the layers of intermetallics and buckling of magnesium layers. The specimens compressed in the perpendicular direction failed by transverse cracking in the intermetallic layers and fallowing catastrophic cracking inclined about 45° to the interface of both intermetallic and magnesium layers. The flexural strength of the composites was higher in perpendicular than in parallel direction. When the load parallel to the layers was applied, the failure occurred by cleavage mode showing limited plastic deformation. When the load perpendicular to the layers was applied, the failure occurred by transverse cracking of the intermetallic layers and gradual cracking of the Mg layers. The Charpy-tested samples showed the same fracture behavior as the bend-tested specimens, which indicated that the same mechanisms operated at both high impact rate and low bending-test rate.